Hydrophobic association hydrogels based on N-acryloyl-alanine and stearyl acrylate using gelatin as emulsifier. Issue 45 (19th April 2016) - Cui, Zhao; Cheng, Ru; Liu, Jie; Wu, Youping; Deng, Jianping
Abstract : Tough chiral hydrogels were established through hydrophobic association, showing optical activity and mechanical properties and possessing potential applications as biomaterials. Abstract : Poly( N -acryloyl-alanine)-based hydrophobic association hydrogels were prepared through free radical polymerization of N -acryloyl-alanine (NAA) with ammonium persulfate as initiator, in which hydrophobic monomer stearyl acrylate underwent simultaneous micellar polymerization in the presence of gelatin as emulsifier. Fourier transform infrared spectra and scanning electron microscopy demonstrated the formation and microscopic structure of the resulting hydrogels. The hydrophobic association enabled the hydrogels to exhibit desirable toughness and could be molded into diverse shapes without breaking. Uniaxial tensile test and cyclic tensile test also demonstrated the high toughness of the hydrogels. The chiral monomer (NAA)-derived polymer chains rendered the hydrogels with optical activity, according to circular dichroism spectra. More fascinatingly, the hydrogels demonstrated shape memory behavior due to the hydrophobic poly(stearyl acrylate) domains. Therefore the tough chiral hydrogels are expected to find significant applications in tissue engineering and other biomedical fields.